PATELLAR HEIGHT EXAMINATION WITH VARIOUS METHODS ON GENU X-RAY: IN A SEARCH OF THE MORE PRECISE COMBINATION - Notariana Kusuma Astuti; Muchtar Hanafi; Amelia Tjandra Irawan; Anistyaning Wahyu Adhie (Biomedika, 2025)
Patellar height, which represents distance formed by the patella and the length of patellar tendon, can predict various knee joint problems. The Insall-Salvati (IS), Caton-Deschamps (CD), and Blackburne-Peel (BP) ratios are widely used to measure patellar height. Those methods conveyed various levels of variability and reproducibility. However, no method perfectly defines the true patellar height in relation to the tibiofemoral joint with high reproducibility and minimal variability. The study involved x-rays of 15 left-knee joints of Indonesian women across various ages without any history of knee injury. Patellar height was measured using the IS, CD, and BP methods (three times of measurement for each method). Patellar height was classified into infera, norma, and alta based on Indonesian measurement standard. The average measurement ratios were analyzed descriptively to obtain the conclusion. The IS ratio identified a patella norma in 14 subjects and a patella infera in 1 subject. The CD ratio indicated 12 subjects with a patella norma, 2 subjects with a patella alta and 1 subject with a patella infera. The BP ratio resulted in a patella norma in 8 subjects and a patella alta in 7 subjects. Discrepancies in the subgroups were varied. Patella norma from IS ratio confirmed by CD and BP ratios resulted in a percentage of 33%. The IS method combined with the CD method yielded a percentage of 67% with p(IS-CD) = 0.915. The combination of IS-BP and CD-BP methods yielded 53% with p(IS-BP) = 0.02 and 40% with p(CD-BP) = 0.052 respectively. The results show a method-dependent disparity in patellar height measurement. Single IS ratio provides a smaller percentage than its combination with CD or BP ratio. The combination with the highest percentage was obtained between IS and CD ratios. This study implied the measurement of patellar height precisely in various genu joint problems, such as predicting progression of patellofemoral osteoarthritis, pain of the genu joint, and luxation or subluxation of the patella. A future study can involve a larger number of subjects.